2010
DOI: 10.1519/jsc.0b013e3181ad4f89
|View full text |Cite
|
Sign up to set email alerts
|

Static Stretching Does Not Impair Performance in Active Middle-Aged Adults

Abstract: Recent investigations with young, healthy adult subjects suggest that static stretching before activity decreases performance and should, therefore, be avoided. The purpose of this study was to assess the effects of an acute static stretching protocol on balance and jump/hop performance in active middle-aged adults. Ten subjects (6 men and 4 women aged 40-60 yr) from a martial arts school volunteered to take part in this research study. This was a repeated measures design. Subjects who stretched for 10 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
0
34
2
2
Order By: Relevance
“…Other studies using 45 s (Gonzalez-Rave et al 2009;Knudson et al 2001;Unick et al 2005), B60 s (Robbins and Scheuermann 2008) and B90 s (Behm et al 2006;Handrakis et al 2010;Samuel et al 2008) of static stretching have also reported no effects on jump heights. Nonetheless, there are more prolonged duration static stretching studies employing 2-8 min that also do not elicit isokinetic torque impairments (Cramer et al 2007a, b;Ryan et al 2008b).…”
Section: Effect Of Stretching Durationmentioning
confidence: 91%
“…Other studies using 45 s (Gonzalez-Rave et al 2009;Knudson et al 2001;Unick et al 2005), B60 s (Robbins and Scheuermann 2008) and B90 s (Behm et al 2006;Handrakis et al 2010;Samuel et al 2008) of static stretching have also reported no effects on jump heights. Nonetheless, there are more prolonged duration static stretching studies employing 2-8 min that also do not elicit isokinetic torque impairments (Cramer et al 2007a, b;Ryan et al 2008b).…”
Section: Effect Of Stretching Durationmentioning
confidence: 91%
“…Although the mechanisms involved were not evaluated, the best gains in range of motion observed in TG180 may be related to the time under tension during muscle stretching. During the aging process, there is a decrease in rigidity of the muscle-tendon unit 16 . Behm et al 17 suggested that a less rigid muscle-tendon unit may accommodate more successfully the stress resulting from stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Behm et al 17 suggested that a less rigid muscle-tendon unit may accommodate more successfully the stress resulting from stretching. Thus, larger volumes of stretching would be needed to promote a better increase in the range of motion of elderly people 16,18 . There was no difference between the two volumes of stretching employed for values of muscle strength, both TG90 and TG180 promoted equally important improvements, 21% and 25% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Em estudo realizado com homens e mulheres de meia-idade (50 anos), Handrakis et al (2010) não encontraram nenhuma alteração nos valores de desempenho muscular, avaliado por meio do teste de salto em distância, após o emprego de três repetições de alongamento com duração de 30s (volume total de 90s). Gurjão et al (2010) e Gonçalves et al (2012) também utilizaram três repetições de 30s de alongamento estático, em mulheres idosas, e não encontraram alterações agudas significativas na produção de força muscular, CVM e na taxa de desenvolvimento de força pico.…”
Section: Efeitos Agudos Do Alongamento Sobre a Função Musculoesquelétunclassified
“…Sabe-se que exercícios de alongamento promovem aumento da complacência da unidade musculotendínea, que pode aumentar o tempo para contração muscular, comprometendo a produção de força (OGURA et al, 2007). O processo de envelhecimento por si só diminui a rigidez das estruturas, as quais, já estando mais complacentes, podem acomodar o estresse decorrente do alongamento e não alterar a produção de força em adultos idosos (HANDRAKIS et al, 2010;BEHM et al, 2006).…”
Section: Efeitos Agudos Do Alongamento Sobre a Função Musculoesquelétunclassified